Growing pains: Paradoxical tensions and vicious cycles in new venture growth. (February 2021) - Es-Sajjade, Abdelghani; Pandza, Krsto; Volberda, Henk
In this article, we explore how paradoxical tensions related to exploration–exploitation dynamics may shape vicious cycles in high-growth ventures. Based on an inductive, interpretive case study at a telecommunications firm in the United Kingdom, we identify a set of drivers through which vicious cycles may emerge and persist over time. While some drivers are associated with originating the vicious cycle (cycle originators), others are associated with sustaining it (cycle perpetuators). Cycle originators identified in the study include tradeoff cognition, structural separation, and a structural leadership void. Cycle perpetuators include intergroup tensions, ineffectual integration, and a temporal leadership void. We show how the interplay between these drivers in a self-reinforcing process culminates in the escalation of tensions and a political turnover (cycle climax). In the field study, we observe the operation of this pattern over two full cycles. Based on the findings, we develop a framework relating paradoxical tensions to vicious cycles in new venture growth. We conclude by challenging traditional stage-based conceptualizations of new venture growth, and by discussing the implications of our study for research on the linkages between organizational paradox, ambidexterity, and venture growth theory.